smileycellist2

2020-11-08

If . Show that

odgovoreh

Step 1
Given data:
The first matrix is $A=\left[\begin{array}{ccc}1& 2& 0\\ 1& 1& 0\\ 1& 4& 0\end{array}\right]$
The second matrix is $B=\left[\begin{array}{ccc}1& 2& 3\\ 1& 1& -1\\ 2& 2& 2\end{array}\right]$
The third matrix is $C=\left[\begin{array}{ccc}1& 2& 3\\ 1& 1& -1\\ 1& 1& 1\end{array}\right]$
Step 2
The multiplication of AB matrices is,
$AB=\left[\begin{array}{ccc}1& 2& 0\\ 1& 1& 0\\ 1& 4& 0\end{array}\right]\left[\begin{array}{ccc}1& 2& 3\\ 1& 1& -1\\ 2& 2& 2\end{array}\right]$
$=\left[\begin{array}{ccc}\left(1+2\right)& \left(2+2\right)& \left(3-2\right)\\ \left(1+1\right)& \left(2+1\right)& \left(3-1\right)\\ \left(1+4\right)& \left(2+4\right)& \left(3-4\right)\end{array}\right]$
$=\left[\begin{array}{ccc}3& 4& 1\\ 2& 3& 2\\ 5& 6& -1\end{array}\right]$
The multiplication of AC matrices is,
$AC=\left[\begin{array}{ccc}1& 2& 0\\ 1& 1& 0\\ 1& 4& 0\end{array}\right]\left[\begin{array}{ccc}1& 2& 3\\ 1& 1& -1\\ 1& 1& 1\end{array}\right]$
$=\left[\begin{array}{ccc}\left(1+2\right)& \left(2+2\right)& \left(3-2\right)\\ \left(1+1\right)& \left(2+1\right)& \left(3-1\right)\\ \left(1+4\right)& \left(2+4\right)& \left(3-4\right)\end{array}\right]$
$=\left[\begin{array}{ccc}3& 4& 1\\ 2& 3& 2\\ 5& 6& -1\end{array}\right]$
The multiplication of AB and AC is equal.
Thus, AB=AC, but B not equal to C.

Do you have a similar question?